IMPROVING NOCOMIT-J PROGRAM AS A RESPONSE OF WOMEN’S AND YOUTH’S SUICIDE CASES SURGE DURING COVID-19 - Kusumadewi, Hemalia (Jurnal Transformasi Global, 2023)
Suicide has been a long-time national problem for Japan as they hold the record for country with highest suicide rate according to WHO and the problem continues as of current. COVID - 19 which impacted most nation throughout the world including Japan, has a hand in influencing the increase of suicide rate in Japan. This increase is particularly evident in groups of youth and women who are among the most vulnerable groups in Japan, thus calls for more comprehensive sets of policy for suicide prevention. Currently there are prevention policies existing curRently. Among them there is a policy called NOCOMIT-J that will be the focus of this article. However, the rapid increase of suicide in pandemic time proves that there is an urgent need to improve the policy to suits the complexity of the situation. This paper aims to assess the variables behind the increase of suicide rates in Japan particularly for youth and women in order to use it as a basis calculation to improve the existing suicide prevention policy to focus on the group-specific problems. This paper will use qualitative method of descriptive case studies to analyze the unique factor contributing to women and youth suicide cases in pandemic time and use the result to suggest improvements for NOCOMIT-J policy by analyzing it in the established  framework of holistic global mental health policy. Keywords: COVID-19; Suicide; Women; Youth